An Analysis of Semiotics in Balenciaga Advertisements - Desy Deria Panggabean; Arsen Nahum Pasaribu; Donna Ria Pasaribu (Merwin Publisher, 2025)
Advertising is one of the media used to promote a product. Balenciaga is one of the fashion brands that is very famous because the advertisements and products displayed have successfully generated controversy. The controversy arises because the signs used in the advertisement seem strange, unusual, and off the mark. These signs are analyzed using Roland Barthes' Theory. The purpose of this research is to find signs along with denotation meaning, connotation meaning, and myth in Balenciaga advertisements. Descriptive qualitative analysis is the method used. The results of the research show that the signs found in Balenciaga advertisements have denotation, connotation, and mythological meanings. The signs represent sexuality issues, war issues, environmental issues, and poverty issues.